Analisis Peran Kepolisian dalam Menanggulangi Prostitusi Online di Kota Kupang - Risna Astuti; Deddy R. Ch. Manafe; Adrianus Djara Dima (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2025)
Purpose of this research aims to find out and explain the function and role of the police in tackling online prostitution in Kupang City, and find out what factors affect the success of the police in tackling online prostitution in Kupang City. This research is a type of empirical research. The source of material from this study is primary legal material obtained from the information or opinions of the respondents, then analyzed qualitatively. The results of this study show that the Role of the Police in Overcoming Online Prostitution in Kupang City. The police's efforts to tackle online prostitution in Kupang City involve prevention, control, and enforcement measures. Prevention is carried out through community disease operations, education, and cyber patrols. Factors Affecting the Success of the Police in Overcoming Online Prostitution in Kupang City. The factors that affect the success of the police in tackling online protests are Internal Factors and External Factors. Suggestion from the author It is hoped that the East Nusa Tenggara police will strengthen and debriefing the police so that legal action against online prostitution is more effective and fair.